Business Strategy to Facing Declining Sales of PT. NMI (The Indonesian Journal of Business Administration, 2019)
Indonesia is the fourth largest population in the world with total population about 265 million.  The advantage of the large population owned by Indonesia has a positive impact on automotive sales. It is estimated that significant growth for automotive occurs in the segment of passenger vehicle (PV), estimated at growth until 2020 reaches 6.8%. The issue is even though total PV sales are increase but PT. Nissan Motor Indonesia was facing declining in sales around 68% in just 3 years. It is necessary to do research to get the right solution for this issue.In this research, the Framework is first, the input explain the business issue, second the process is explaining about business exploration, and third the outputs explaining business solution. In the business exploration, use internal & external analysis, and find the main rootcause use fish bone analysis. For business solution find the best alternative use SWOT and TOWS matrix analysis for generate alternative, then choosing the best alternative will use AHP process. As a result, the main factor that affect to the declining sales of Nissan are turn over new model is too long plus and expensive spare part for maintain Nissan cars. Then for improve this condition, Nissan could be launch new model that build from alliance plant & improve total delivery cost and integrating part supply with alliance plant. Keywords: Decline in sales, internal & external analysis, SWOT & TOWS, AHP, launch new model, Alliance